Trial in progress: phase I study of non-viral gene-modified CAR-T cell therapy for malignant solid tumors expressing EPHB4 receptor (CARTiEr) - Funasaka, Chikako; Naito, Yoichi; Kubota, Hitomi; Ishiguro, Yukiko; Fuse, Nozomu; Wakabayashi, Masashi; Sato, Akihiro; Yuda, Junichiro; Ishii, Genichiro; Suzuki, Toshihiro; Takenouchi, Kazumasa; Nakatsura, Tetsuya; et al. (Frontiers in Oncology, 2025)
BackgroundEphrin type-B receptor 4 (EPHB4) is overexpressed on the surface of various tumor cells, including cells from malignant bone and soft-tissue tumors. AP8901 CAR-T cell therapy can specifically recognize and kill EPHB4 receptor-expressing malignant tumor cells by modifying the natural EPHB4 receptor ligand, ephrin B2. AP8901 is being developed via genetic manipulation involving the “piggyBac transposon” and “genetically modified feeder cell” methods, which enables the stable expression of CAR proteins in T cells and prevents T cell exhaustion. AP8901 has demonstrated therapeutic efficacy and tolerability in mice transplanted with rhabdomyosarcoma cells. We planned a phase I study to evaluate the safety and efficacy of AP8901 for metastatic solid tumors.MethodsThis is a single-center, single-arm, dose-escalation, phase I study to evaluate the safety, tolerability, pharmacokinetics/pharmacodynamics, and preliminary anti-tumor activity of a single intravenous dose of AP8901 in patients with Ewing sarcoma or solid tumors expressing the EPHB4 receptor. Key inclusion criteria include the following: subjects with histologically diagnosed Ewing sarcoma or solid tumor with confirmed metastasis or recurrence/no standard treatment for metastasis or recurrence, or refractory or intolerant to standard treatment; measurable or evaluable disease according to the Response Evaluation Criteria in Solid Tumors (RECIST) version 1.1; recent biopsy or surgical resection specimens with prescreening immunohistochemistry positive for EPHB4 in ≥1% of tumor cells; ECOG performance status 0 or 1; and subjects expected to survive ≥3 months from the date of enrollment. This study is being conducted at the National Cancer Center Hospital East, Japan.DiscussionThe advantage of AP8901 is that it is expected to prevent T cell exhaustion and maintain its anti-tumor effect. This phase 1 study of AP8901 will provide new evidence for the application of this novel CAR-T cell therapy in patients with solid tumors, including Ewing sarcoma.